From the Editors - Eden, Dov (Academy of Management Journal, 2002)
A letter from the editor is presented which discusses the role of meta-analysis and replication research in the articles submitted to the periodical for review. The author points out that the journal uses the idea of articles having an important contribution to the field of management as a basis for review. This leads many of the articles to contain information on relatively new ideas, even though some of those ideas contain information of little importance. For this reason, the periodical accepts articles containing replication research and meta-analysis.